Mitigating Cybersecurity Risks in E-Waste: A Study on Secure Disposal Practices in Tanzania’s Public Institutions - Mustapha, Athuman; Mgawe, Bonny S; Mvulla, Jaha; Sam, Anael (Journal of Information Systems and Informatics, 2025)
The growing volume of electronic waste (e-waste) in Tanzanian public institutions poses serious cybersecurity risks, as discarded devices often contain sensitive data vulnerable to unauthorized access. This study examines these risks across 11 public institutions, involving IT staff, e-waste handlers, policymakers, and environmental officers. It applies Routine Activity Theory, a framework that explains risks as arising when cybercriminals exploit unsecured e-waste due to weak regulations. Through interviews and focus group discussions, the research identifies key vulnerabilities: data leakage from improper sanitization, regulatory gaps, and risks from informal disposal methods like auctions. These findings highlight the need for stronger oversight to prevent data breaches. The study proposes a framework that categorizes devices by risk level and integrates secure sanitization protocols, such as data wiping or destruction. Policymakers and institutions must urgently adopt these protocols to protect sensitive data and promote sustainable e-waste management in Tanzania’s public sector.
Keywords: cybersecurity, e-waste disposal, Routine Activity Theory (RAT), data leakage, institutional guardianship, Tanzania.